"More Practice-based Courses and Not Just a Load of Papers to Read": Youth Soccer Coaches Reflections on Coach Education Programs in Sweden - Hertting Krister (Sciendo, 2019)
In Sweden, the formal soccer coach education programs are divided into different levels and are also divided into youth coaching and senior coaching. This paper focuses on youth soccer coaches and their reflections on coach education programs. In the background section the Swedish context is described, as well as current research on coaches' education and learning. The aim of the paper was to investigate youth soccer coaches' reflections on coach education programs and to analyse their reflections by using a cultural approach to learning. The empirical material of the paper derives from a web-based questionnaire, posing questions about competence, learning and stress. The coaches were also invited to reflect on the question "how do you believe that soccer associations can educate good coaches?" There were 369 responses, and these were analysed using qualitative content analysis. Results indicated reflections about Flexibility in time, place and content, Mentorship supporting informal learning, Demanding mandatory education and emolument, Education focusing on wholeness and Education being based in practice. The conclusion was that decentralization of education and development of coaches' contexts, abilities and motivation to critically analyse aims and contents of coach education programs are improvement areas for learning and coaching practices.